Enhanced visible-light-driven photocatalytic performance for degradation of organic contaminants using PbWO4 nanostructure fabricated by a new, simple and green sonochemical approach - Zinatloo-Ajabshir, Sahar; Baladi, Mahin; Salavati-Niasari, Masoud (Ultrasonics sonochemistry, 2021)
•Spindle shaped PbWO4 nanostructure with enhanced photocatalytic activity was obtained by facile and green sonochemical way for the first time.•Maltose as a new capping agent was utilized.•Sonication time, dose of precursors, power of ultrasound waves and kind of capping agent were optimized.•The made lead tungstate samples in role of visible-light photocatalyst were applied to remove organic pollution in water.•Usage of ultrasonic irradiation has remarkable effect on performance of PbWO4 photocatalyst for decomposition. Water contamination has turned into a critical global concern that menaces the entire biosphere and has a notable effect on the lives of living beings and humans. As a proper and environmentally friendly solution, visible-light photocatalysis technology has been offered for water contamination removal. There is a strong interest in the design of the efficient catalytic materials that are photoactive with the aid of visible light. Herein, to fabricate a highly efficient photocatalyst for removal of organic pollution in water, a facile and swift sonochemical route employed for creation of the spindle shaped PbWO4 nanostructure with the aid of an environmentally friendly capping agent (maltose) for the first time. To optimize the efficiency, dimension and structure of lead tungstate, various effective factors such as time, dose of precursors, power of ultrasound waves and kind of capping agents were altered. The attributes of PbWO4 samples were examined with the aid of diverse identification techniques. The produced lead tungstate samples in role of visible-light photocatalyst were applied to remove organic pollution in water. The kinds of pollutants, dose and type of catalyst were examined as notable factors in the capability to eliminate contaminants. Very favorable catalytic yield and durability were demonstrated by spindle-shaped PbWO4 nanostructure (produced at power of 60 W for 10 min and with usage of maltose). Usage of ultrasonic irradiation could bring to improvement of catalytic yield of PbWO4 to 93%. Overall, the outcomes could introduce the spindle-shaped PbWO4 nanostructure as an efficient substance for eliminating water contamination under visible light.